2009
DOI: 10.1159/000236367
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Nucleus Location: Relationships between Stereotactic AC-PC-Based Diagrams and MRI Anatomy-Based Contours

Abstract: Subthalamic nucleus (STN) targeting is classically performed based on AC-PC probabilistic position. Nevertheless, MRI allows direct visualization and targeting. We aimed to compare the position localized on MR images with standard stereotactic diagrams. The STN was manually contoured on MR images (22 Parkinson’s disease patients); boundaries were simplified in a schematic polygonal form. Front and lateral stereotactic diagrams were constructed according to Talairach and Benabid. We compared x, y and z coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 98 publications
1
13
0
1
Order By: Relevance
“…Our findings are consistent with those of Caire et al [8], who found significant discordance between MRI-based polygons and AC-PC-based images and that the subthalamic nucleus was more posterior, medial, and slightly inferior on MRI images. Because of the small size, the convex lens shape, and the oblique path of the subthalamic nucleus, precise localization of the nucleus by imaging studies is rather challenging.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of Caire et al [8], who found significant discordance between MRI-based polygons and AC-PC-based images and that the subthalamic nucleus was more posterior, medial, and slightly inferior on MRI images. Because of the small size, the convex lens shape, and the oblique path of the subthalamic nucleus, precise localization of the nucleus by imaging studies is rather challenging.…”
Section: Discussionsupporting
confidence: 93%
“…Caire et al [21] aimed to compare the STN position localized on MRIs with standard stereotactic diagrams. The STN was manually contoured on MRIs (22 PD patients); boundaries were simplified in a schematic polygonal form.…”
Section: Discussionmentioning
confidence: 99%
“…The anteroposterior coordinate of the STN center is indeed -3.8 8 1.3 mm from the MCP for Richter et al [10] , -1.26 8 1.06 mm for Schlaier et al [11] , -1.1 8 2.3 mm (right side) and -0.6 8 1.8 mm (left side) for Slavin et al [8] , and -2.6 8 0.9 mm for Caire et al [12] .…”
Section: Direct Identification Of the Stn On High-field Axial Mr Imagmentioning
confidence: 96%